Peran Mahasiswa KKN dalam Implementasi Rocket Stove Sebagai Solusi Pengelolaan Sampah untuk Peningkatan Kualitas Lingkungan di Desa Cinanggela, Kecamatan Pacet, Kabupaten Bandung: Pengabdian - Annisa Shafa’ Lathifah; Neneng Nurbaeti Amien; Nazma Aliyah Nurafifah; Muamar Ridho Firdi Aulia; Hilwa Syahda Naabillah; Aryo Nur Ashifa; Gevira Indria Syahla; Dika Arya Pratama; Aulia Agnia; Muhammad Ra’is Al-Ghassani; Muhammad Zahid Khoerulloh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community Service (KKN) is a form of student community service that is an implementation of the Tri Dharma of Higher Education. This activity is designed to empower the community through the application of knowledge gained during the lecture period. The focus of this service is on the role of KKN students in implementing Rocket Stove as a waste management solution to improve environmental quality in Cinanggela Village, Pacet District, Bandung Regency. In this village, there are still obstacles in waste management that have implications for environmental quality. Through the KKN program, students strive to make a real contribution by implementing Rocket Stove which can convert waste into an environmentally friendly alternative energy source. The results of the activity show that this program contributes significantly to increasing public awareness of the importance of waste management and has a positive impact on the cleanliness and quality of the village environment.